Entre as coisas, as pessoas e as memórias: uma análise da educação patrimonial e da compreensão do bem arqueológico no Vale dos Sonhos em Goiânia/GO - Pinheiro, Venúsia Cele Ferraz (2006)
The "Archaeological Patrimony and Heritage Education" was this work's subject, that aimed to analyze the understanding of the educative actions developed at the "Archaeological Rescue of the Vale dos Sonhos Site Project, Goiânia - GO" made between 2001 and 2003 at Vale dos Sonhos Condominium Area by experts from Universidade Católica de Goiás. Mainly intending to exam the public comprehension - people who participated of the mentioned actions - about the cultural and archeaological heritage placed in that region, and also reflect on the valorization of this heritage by the local population, that was made interviews with twenty inhabitants of the Vale dos Sonhos Condominium Area, those people who activitly participated of the educational process. This is an exploratory and descriptive case study, whose research instruments were the semistructured interview and documentary analysis. The technique for studying the results was the speech graphic analysis.